A Rapid Approach for Identifying Cell Lines Lacking Functional Cytidine Deaminase - Ligasová, Anna; Kociánová, Markéta; Koberna, Karel (International journal of molecular sciences, 2025)
CDD plays a pivotal role within the pyrimidine salvage pathway. In this study, a novel, rapid method for the identification of cell lines lacking functional cytidine deaminase was developed. This innovative method utilizes immunocytochemical detection of the product of 5-fluorocytidine deamination, 5-fluorouridine in cellular RNA, enabling the identification of these cells within two hours. The approach employs an anti-bromodeoxyuridine antibody that also specifically binds to 5-fluorouridine and its subsequent detection by a fluorescently labeled antibody. Our results also revealed a strong correlation between the 5-fluorouridine/5-fluorocytidine cytotoxicity ratio and cytidine deaminase content. On the other hand, no correlation was observed between the 5-fluorouridine/5-fluorocytidine cytotoxicity ratio and deoxycytidine monophosphate deaminase content. Similarly, no correlation was observed between this ratio and equilibrative nucleoside transporters 1 or 2. Finally, concentrative nucleoside transporters 1, 2, or 3 also do not correlate with the 5-fluorouridine/5-fluorocytidine cytotoxicity ratio.
Keywords: 5-fluorocytidine deamination; Cytidine; cytidin; cytidine deaminase; buněčné linie; Cytidine Deaminase; Cell Line; equilibrative and concentrative nucleoside transporters; lidé; cytidindeaminasa; uridin; Uridine; Humans; 5-fluorouridine